Democracy in Africa: Theoretical models Towards Indigenous Governance - Ukaegbu, Chidi O.; Idowu, Akinwumi OJO; Chukwuma, Ogonna E. (Social Science Research, 2024)
Several attempts have tried to estimate and document the character of liberal democracy and its impact on the condition of states in Africa. One lesson from the past research is the justification of the positive impact of this model of governance in Africa not minding the fact that it has proven incapable of transforming the African state. In this paper, we attempt to reassess this impact in contrast with indigenous theoretical models that conform with African peculiarities to governance prior to the introduction of western democracy in the light of the continuous subjugation of Africa in various forms. Employing a fixed effect approach and documentary evidence found in the works of indigenous Political thought in the works of outstanding African theorists and leaders, our finding shows that western democracy has proven incapable of transforming Africa. It shows further that African theorists and leaders have steadily advocated a sharp return to Africa's profound democratic governance models prior to the introduction of western democracy. This according to the study, has the capacity to sustain Africa and make it relevant in the comity of nations. This advocacy and its application would lay to rest the claim that Africa had no governance models and democratic principles that can sustain its continuous existence before and after western invasion.